A low-calorie diet raises β-aminoisobutyric acid in relation to glucose regulation and leptin independent of exercise in women with obesity - Faiz, Habiba; Malin, Steven K. (Frontiers in Physiology, 2023)
Introduction: β-aminoisobutyric acid (BAIBA) is a suggested cytokine secreted from skeletal muscles that regulates insulin sensitivity, pancreatic function, and fat oxidation. However, no studies to date have examined if a low-calorie diet (LCD) or LCD + with interval exercise (LCD + INT) differentially raises BAIBA. The purpose was to examine if LCD or LCD + INT raises circulating BAIBA in relation to cardiometabolic health. Methods: For this, twenty-three women with obesity were randomized to either 2-weeks of LCD (n = 12, 48.4 ± 2.5 y, 37.84 ± 1.5 kg/m2; ∼1200 kcal/day) or LCD + INT (n = 11, 47.6 ± 4.3 y, 37.9 ± 2.3 kg/m2; ∼60 min/d of INT alternating 3 min of 90% and 50% HRpeak), with matched energy availability. Fasting BAIBA and adipokines along with glucose, insulin, C-peptide, and FFA after every 30 min up to 120 min were obtained during a 75 g OGTT to estimate total area under the curve (tAUC), insulin sensitivity (SIIS), pancreatic function [disposition index (DI)], and hepatic insulin clearance (HIC). Fuel use (indirect calorimetry) was tested at 0, 60, and 120 min of the OGTT along with fitness (VO2peak) and body composition (BodPod). Results: Both treatments lowered body weight (p < 0.001) and leptin (p < 0.001) but raised BAIBA (p = 0.007) and insulin sensitivity (p = 0.02). LCD + INT increased VO2peak (p = 0.02) and REE tAUC120min (p = 0.02) while LCD and LCD + INT decreased carbohydrate oxidation (CHOox) tAUC120min (p < 0.001). Increased BAIBA associated with reduced weight (r = −0.67, p < 0.001), leptin (r = −0.66, p = 0.001), CHOox tAUC120min (r = −0.44, p = 0.03) and DImuscle120min (r = −0.45, p = 0.03), but elevated HIC120min (r = 0.47, p = 0.02). Discussion: Concluding, LCD and LCD + INT increased BAIBA in relation to reduced body weight and pancreatic function in women with obesity. This suggests energy deficit is a key factor regulating circulating BAIBA.